2023
DOI: 10.1037/cpb0000232
|View full text |Cite
|
Sign up to set email alerts
|

“We do not see color!”: How executive coaching can help leaders to create inclusive corporate cultures by acknowledging structural racism in its ecosystem.

Abstract: While leaders are scrambling to take up the issue of diversity and inclusion in the context of the heightened consciousness of systemic and structural racism prompted by the Black Lives Matter campaign, the world of coaching has been slow to engage with the issue of racial justice. This year-long qualitative study responds to a gap in coaching literature, which is currently silent on the impact of systemic racism on coaching practice. In this paper we focus on the views and experiences of coaches who identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Effectively creating diverse, equitable, and inclusive (DEI) spaces to build a sense of belonging for BIPOC (Black, Indigenous, and People of Color) employees in America has been a challenge that organizations have attempted to address over the past several decades. The issue is costly and harmful to ignore and has recently moved to the forefront once again (Roche & Passmore, 2023, Akpapuna et al, 2020, Brown et al 2022, Nayani, 2021, Chandler, 2021, Evans, 2019, Brecheisen, 2023, Houston, 2021, The impact of belonging and the cost of exclusion, 2022, Ray, 2021). Since 2020, and a global pandemic, people have become more outwardly involved with social justice movements, protests, and other political engagements (Roche & Passmore, 2023, Akpapuna et al, 2020, Brown et al 2022.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectively creating diverse, equitable, and inclusive (DEI) spaces to build a sense of belonging for BIPOC (Black, Indigenous, and People of Color) employees in America has been a challenge that organizations have attempted to address over the past several decades. The issue is costly and harmful to ignore and has recently moved to the forefront once again (Roche & Passmore, 2023, Akpapuna et al, 2020, Brown et al 2022, Nayani, 2021, Chandler, 2021, Evans, 2019, Brecheisen, 2023, Houston, 2021, The impact of belonging and the cost of exclusion, 2022, Ray, 2021). Since 2020, and a global pandemic, people have become more outwardly involved with social justice movements, protests, and other political engagements (Roche & Passmore, 2023, Akpapuna et al, 2020, Brown et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…
Efforts to establish diverse, equitable, and inclusive (DEI) spaces within organizations, particularly for BIPOC (Black, Indigenous, and People of Color) employees, have gained renewed attention amidst societal shifts towards social justice (Roche & Passmore, 2023, Akpapuna et al, 2020, Brown et al 2022. Despite extensive literature on DEI initiatives, there remains a gap in understanding BIPOC members' perceptions and experiences within White-dominated workspaces.
…”
mentioning
confidence: 99%
“…Few coaching studies have included race as a factor. As a result, there is a general lack of data about representation, participation or activity of coaches of colour in the global coaching community (Roche & Passmore, 2021;Roche & Passmore, 2023a;Roche & Passmore, 2023b) or the importance of identity in the coaching relationship to groups who in many economies have experienced sustained direct and, more latterly, indirect and structural discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…What’s It Mean? Implications for Consulting PsychologyEvidence suggests that culturally congruent models of coaching are needed to improve coaching efficacy with African Americans (Kea-Edwards, 2023) and that coaches and organizations must be more willing to directly address issues of racism and systemic bias (Bendel & Passmore’s, 2023; Carter et al, 2023; Kafka, 2023; Kea-Edwards, 2023). Qualitative and quantitative research has identified tools and interventions that can enable coaching efficacy and ultimately individual readiness for promotion.…”
mentioning
confidence: 99%
“…Roche and Passmore’s (2023) study provides a global perspective on coaching. Using a focus-group methodology, they sought to understand how issues of systemic racism and social justice showed up as topics in practice and how these issues were addressed.…”
mentioning
confidence: 99%